1978
DOI: 10.1042/bj1700569
|View full text |Cite
|
Sign up to set email alerts
|

The lability of the products of mitochondrial protein synthesis in Saccharomyces cerevisiae. A novel method for protein half-life determination

Abstract: A method for the determination of the half-life of mitochondrial translation products in yeast in vivo is proposed. The method uses inhibitors of cytoplasmic and mitochondrial protein synthesis and is based on double-labelling pulse-chase techniques, the second label being used to estimate 'post-incorporation' during the 'chase'. For the first time the difference between post-incroporation and the widely known recycling of the label is considered. These studies show that, in the turnover of mitochondrial trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…However calculations of turnover rates allowing for post-incorporation and recycling of radioactive label has led to the finding that in S. cereuisiae, the half-life of products of mitochondrial protein synthesis is much shorter than thought in [9], -1 h. In many cases of reports of synthesis of RNA and total protein during the cell cycle, infrequent sampling may have resulted in over-simplified interpretation of observed patterns. In the present investigation, the generation time of 8 h (compared with ~1-3 h for many bacteria and yeasts) has facilitated fairly high resolution of the events occurring during the period of growth and division of A. castelhnii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However calculations of turnover rates allowing for post-incorporation and recycling of radioactive label has led to the finding that in S. cereuisiae, the half-life of products of mitochondrial protein synthesis is much shorter than thought in [9], -1 h. In many cases of reports of synthesis of RNA and total protein during the cell cycle, infrequent sampling may have resulted in over-simplified interpretation of observed patterns. In the present investigation, the generation time of 8 h (compared with ~1-3 h for many bacteria and yeasts) has facilitated fairly high resolution of the events occurring during the period of growth and division of A. castelhnii.…”
Section: Discussionmentioning
confidence: 99%
“…While these oscillations in levels of adenine nucleotides contravene the hypothesis of stabilized adenylate charge [8], such changes predict variations in the balance between energy-utilizing and energy-synthesizing pathways 181. Also, the recent finding that the half-life of products of mitochondrial protein synthesis in Saccharomyces cereElsevierlNorth-Holland Biomedical Press visiae is -60 min [9] open to question the belief that the sequence of events leading to the accumulation of new cellular material during rapid cell growth is entirely directed towards biosynthesis. This investigation reports the changes in RNA and total cell protein levels during synchronous growth of A. castellanii and shows that the cell cycle may be divided into a number of subcycles of biosynthesis and degradation in which energy-utilization is tightly coupled to energy generation.…”
Section: Introductionmentioning
confidence: 99%
“…After 60 min at 37'C, the reaction was terminated by successive additions of 100 fl of the above buffer, 100 ~1 of albumin solution (0.48 mg protein), and 100 ti of 50% trichloroacetic acid. Radioactivity of the 20 000 x g supernatant was determined as previously [3]. This problem does not arise in works with eukaryotic microorganisms.…”
Section: Methodsmentioning
confidence: 99%
“…A high turnover of mitochondrial translation products (half-life approximately 60 min) in isolated yeast mitochondria was observed for the first time by Bakalkin et al (1978). In 1979, Kalnov et al reported that one-third to one-half of the proteins synthesized in isolated yeast mitochondria were degraded with a half-life of about 35 min (Kalnov et al 1979b).…”
Section: Degradation Of Mitochondrial Translation Productsmentioning
confidence: 99%